2003
DOI: 10.1080/00207450390220349
|View full text |Cite
|
Sign up to set email alerts
|

Leukoaraiosis in Stroke Patients

Abstract: Pathogenesis of leukoaraiosis (LA) is not clearly understood and its significance in patients with stroke remains undetermined. In the Neurology Department of Ankara Hospital, computed tomography (CT) examination of brain was performed for various reasons in 288 patients. LA was detected in 178 patients by the use of brain CT. Patients with LA had a higher incidence of hypertension history (70.8%) when compared with the non-LA group (57.3%; p <.05). There was no statistically significant difference in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In contrast, the Scheltens scale, which was used in the present study, is able to detect small amounts of WML [15]. Furthermore, other studies were not designed to specifically assess the effects of DM on neuro-imaging modalities but assessed the effect of DM in selected patients with stroke or other cardiovascular risk factors [2, 5, 7, 9]. The results of these studies have low external validity and do not allow to generalize to the DM population visiting an out-patient clinic.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…In contrast, the Scheltens scale, which was used in the present study, is able to detect small amounts of WML [15]. Furthermore, other studies were not designed to specifically assess the effects of DM on neuro-imaging modalities but assessed the effect of DM in selected patients with stroke or other cardiovascular risk factors [2, 5, 7, 9]. The results of these studies have low external validity and do not allow to generalize to the DM population visiting an out-patient clinic.…”
Section: Discussionmentioning
confidence: 65%
“…Two population-based studies demonstrated a relation of DM with cerebral atrophy, whereas an association with WML was not found [3, 6]. Most other studies used dichotomous or ordinal rating scales, which may be not sensitive enough in the discrimination between various degrees of WML [2,7,8,9,10]. This might be important, because the consistently reported modest cognitive deficits in DM patients do not suggest severe lesions and the used scales may therefore underestimate WML in DM patients [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 46 articles, 3 study populations included only type 1 diabetic patients, 2 included only type 2 diabetes, 32 were classified as "predominantly type 2 diabetes," and 9 were classified as "diabetes of unknown type" (Tables 1-3). The diagnosis of diabetes was based on history or medication use in 20 studies (7,8,14,18,20,21,24,26,28,(31)(32)(33)(37)(38)(39)(40)(41)(42)(43)(44), while in the other studies, active screening was done by fasting glucose levels, random glucose levels, or an oral glucose tolerance test. Only two studies included data on metabolic control (16,36).…”
Section: Relation Of Ct and Mri Findings To Cognition And Other Diseamentioning
confidence: 99%